Antidepressant Use in Medicaid-Insured Youth: Trends, Covariates, and Future Research Needs - Zito, Julie M.; Pennap, Dinci; Safer, Daniel J. (Frontiers in Psychiatry, 2020)
Abstract Background: Little research on long-term antidepressant trends within a single large US Medicaid population of youth has heretofore been reported. Methods: Administrative claims data for eight annual timepoints across 28 years were organized for youth (< 20 years old) who were continuously enrolled during the study year in a mid-Atlantic state Medicaid program. Total annual prevalence and age-, gender-, race- and eligibility group-specific prevalence were formed from bivariate analyses; logistic regression assessed the change in use (2007-2014) adjusted for covariates. ATD-polypharmacy data were assessed in 2014. Results: The major findings are: 1) ATD use in state Medicaid enrollees grew 14-fold between 1987 and 2014, making up for a substantial drop that followed the FDA suicidal warning of 2004. Data from 2014 revealed significantly increased odds of youth with ATD dispensings compared to 2007 (AOR=1.04 95% CI 1.01-1.07), with a predominance of SSRI/SNRIs (78%). 2) Recent ATD increases were greatest for 15-19-year olds. 3) ATD use in girls passed up ATD use in boys for the first time in 2014. 4) In 2014, ATDs for foster care (12.7%) was 6 times greater than for their income-eligible Medicaid-counterparts. 5) In 2014, a quarter of ATD-medicated youth were diagnosed with a behavior disorder. 6) Twenty percent of ATD medicated Conclusions: Second-generation antidepressant use in Medicaid-insured youth continues despite growing questions that pediatric ATD benefits may not outweigh harms in large subpopulations. Publicly funded, independent investigator-conducted post-marketing surveillance research is needed.